Automatic voltage stability analysis in the presence of contingency: article / Nor Ayuni Ahadiah Ab. Wahab - Ab. Wahab, Nor Ayuni Ahadiah (2011)
This thesis presents an automatic voltage stability analysis in the presence of contingency. In this case, the study was conducted under generator and/ or line outage contingency. The study aims to evaluate the bifurcation point when voltage stability is highly affected by reactive power generation saturation phenomena. The reactive power generation saturation of a unit can change the system voltage immediately from stable to unstable. The value is determined using MATLAB programming that uses fast voltage stability index (FVSI) as an indicator. The results of the index before and after the contingency are compared to show the effect of contingency to the system. The method was tested on the IEEE 30-Bus Reliability Test System (RTS) system and results have been compared using the V-Q curves. Results obtained from study would be beneficial as future referring for researchers and students in power system.